2021
DOI: 10.31665/jfb.2021.14265
|View full text |Cite
|
Sign up to set email alerts
|

Are omega-3 fatty acids efficacious in the treatment of depression? A review

Abstract: The hypothesis that omega-3 fatty acids may play a role in preventing and treating depression is based on correlative associations between fish consumption, omega-3 fatty acid intake and the prevalence of major depressive disorder. Reduced omega-3 fatty acid erythrocyte levels have been found in individuals with depressive disorders. These observational findings are unable to establish a causal relationship between omega-3 fatty acids and depression. The results of randomized controlled trials of omega-3 fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 142 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that almond oil is rich in unsaturated fatty acids and other phytochemicals (Özcan et al ., 2011; Banjanin et al ., 2020). Unsaturated fatty acids from oil extract are tightly linked to antioxidant properties (Parry et al ., 2005; Li et al ., 2016a; Lange et al ., 2021). Although the contents of fatty acids may vary depending on different almond genotype (Özcan et al ., 2020), the fatty acid profile was mainly composed of unsaturated fatty acids including oleic acid, linoleic acids and palmitic acid in the study of 12 almond variants in Siberia (Banjanin et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that almond oil is rich in unsaturated fatty acids and other phytochemicals (Özcan et al ., 2011; Banjanin et al ., 2020). Unsaturated fatty acids from oil extract are tightly linked to antioxidant properties (Parry et al ., 2005; Li et al ., 2016a; Lange et al ., 2021). Although the contents of fatty acids may vary depending on different almond genotype (Özcan et al ., 2020), the fatty acid profile was mainly composed of unsaturated fatty acids including oleic acid, linoleic acids and palmitic acid in the study of 12 almond variants in Siberia (Banjanin et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 fatty acids have also been found to prevent and decrease depression-like behaviors in rat models. However, it's important to remember that most animal models of major depressive illness have significant flaws, especially when it comes to depression subtypes, TRD, and recurrent depression (Lange et al, 2021).…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“… 9 Furthermore, various nutrients and food bioactive have been proposed as effective measures in the management of common mental disorders. 10 , 11 However, evidence of their clinical efficacy is lacking 12 , 13 and their long-term administration may even be harmful. 14 …”
mentioning
confidence: 99%